Intrapartum prediction of emergency delivery due to non-reassuring fetal status at 40 weeks' gestation in low-risk pregnancies: contribution of Doppler parameters, maternal history, and intrapartum clinical characteristics. (2nd September 2021) - Crovetto, Francesca; Cesano, Nicola; Rossi, Federica; Acerboni, Stefano; Marinis, Stefano D. E.; Basso, Annachiara; Martinez Portilla, Raigam Jafet; Acaia, Barbara; Fedele, Luigi; Ferrazzi, Enrico; Persico, Nicola
Abstract: Objective: To assess the added value of Doppler parameters, maternal history, and intrapartum clinical characteristics for the prediction of emergency delivery due to non-reassuring fetal status in low-risk pregnancies. Methods: This was a prospective cohort of low-risk pregnancies undergoing ultrasound assessment at 40 weeks' gestation within 7 days of delivery. The main outcome was emergency cesarean section due to non-reassuring fetal status. The association between Doppler parameters, intrapartum clinical characteristics, and maternal history was performed by logistic regression. The predictive performance of the constructed models was assessed by receiver operating characteristic (ROC) curve analysis and the area under the curve (AUC). Results: From 403 included pregnancies, 18.6% ( n = 75) underwent an emergency delivery due to non-reassuring fetal status. The mean gestational age at birth was 40.5 (SD 5) days. Middle cerebral artery pulsatility index (MCA) and cerebroplacental ratio (CPR) were lower in the emergency cesarean section group (1.16 versus 1.30; p < .001, and 1.61 versus 1.78; p = .001, respectively). There was a higher incidence of small-for-gestational-age neonates (20 versus 10.1%; p = .017), lower Apgar scores at the 5th minute (9.7 versus 9.9; p = .006), and NICU admissions (9 versus 3%; p = .016) in the emergency cesarean section group. The base model comprised nulliparity, and the finding of meconium-stained amniotic fluid during labor, achieving an AUC of 66%, while the addition of the MCA Z-score significantly improved the previous model (AUC: 73%; DeLong: p = .008). Conclusions: In low-risk pregnant woman at term, the addition of MCA Z-score to a previous model comprising maternal history and intrapartum clinical findings, significantly improves the prediction of emergency delivery due to non-reassuring fetal status.